Total knee arthroplasty exhibits satisfactory long-term clinical efficacy in the treatment of hemophilia patients with stiff knees - Liu, Yi; Liu, Yi-fan; Meng, Hong-zheng; Sun, Tao; Gao, Ping; Li, Zhao-zhi; Zhang, Wen-qiang (Frontiers in Surgery, 2023)
Objective: To determine the mid-to-long-term clinical efficacy of total knee arthroplasty (TKA) in the treatment of hemophilia patients with knee stiffness. Methods: The clinical data of 71 patients (78 knees) with hemophilia and concomitant knee stiffness who had undergone TKA between September 2007 and June 2018 were retrospectively analyzed. All patients were male, their mean age at the time of surgery was 38.4. ± 7.9 years of age, and the mean follow-up time was 8.7 years. To determine the effect of stiffness severity on clinical outcomes, the participants were categorized into two groups: severe (preoperative range of motion [ROM]: < 50°, 34 knees) and moderate (preoperative ROM: 50–90°, 44 knees). Their post-TKA clinical and radiological outcomes, quality of life, complications, and long-term survival were assessed. Results: Flexion contracture improved from 23.2°before surgery to 5.9°upon final follow-up, the Knee Society Score (KSS) increased from 31.4 to 74.9, and the KSS functional score increased from 37.6 to 81.4. The mean ROM improved from 54.6° preoperatively to 80.9° postoperatively. The 36-Item Short Form Survey physical and mental scores also improved significantly, with statistically significant differences before and after surgery. The following postoperative complications occurred in 10 knees (12.8%): hemarthrosis (n=3), stiffness (n=4), superficial infection (n=1), skin necrosis (n=1), and periprosthetic infection (n=2), and revision TKA was performed on two knees. The 5- and 10-year survival rate of the prostheses were 98.5% and 93.7%, respectively. The severe group used varus-valgus constrained or hinged prostheses more frequently (52.8% vs. 18.1%), had worse postoperative ROM and functional scores, and had more complications (18.9% vs. 9.0%) than the moderate group. Conclusion: TKA exhibits satisfactory mid-to-long-term efficacy in patients with hemophilic knee joint disease involving preoperative stiffness, thus potentially providing a significant improvement in function and reducing pain. Furthermore, severely stiff knee joints have worse clinical outcomes and more complications than moderately stiff knee joints.